Influence of heated forming tools on corrosion behavior of high strength aluminum alloys. Issue 2 (1st October 2020) - Heider, B.; Scharifi, E.; Engler, T.; Oechsner, M.; Steinhoff, K.
Abstract: In this study forming tools temperated at 24 °C and 350 °C were used to systematically investigate the influence of different cooling rates on the mechanical and corrosion properties of a high strength aluminum alloy AA7075 within a novel thermo‐mechanical process that combines forming and quenching simultaneously. The samples formed within heated tools reveal higher ductility and lower material strength compared to the parts processed in cold tools. In addition, the corrosion behavior changed between samples formed with 24 °C forming tools and 350 °C forming tools, respectively. Through cyclic polarization in chloride containing aqueous media a change in the hysteresis and shift of open circuit potential was observed. Metallographic investigation revealed that there was also a very different corrosion morphology for the samples formed within the heated tools. No change in average grain size could be detected but changes of the microstructure in subgrain scale that occur during the forming within the heated tools are responsible for this effect. In further research, the effect of various cooling rates on mechanical and corrosion behavior and the microstructure will be investigated by variation of the forming tool temperature. Abstract : Hot forming of aluminum alloy AA7075 in heated forming tools influences the resulting microstructure and the mechanical and corrosion properties even after subsequent artificial aging to T6 condition. Through this novel thermo‐mechanical forming route the yield strength and ductility can be modified. Additionally, the changed corrosion behavior in 0.1 % NaCl solution is considered and discussed. Translation abstract: Die Einflüsse der Temperatur von Umformwerkzeugen bei 24 °C bzw. 350 °C zur Kontrolle der Abkühlgeschwindigkeit bei einem innovativen Ansatz der Warmumformung der Aluminiumlegierung AA7075 auf mechanische Eigenschaften und das Korrosionsverhalten wurden systematisch untersucht. Durch erwärmte Umformwerkzeuge konnte erhöhte Duktilität bei verringerter Zugfestigkeit dieser Proben im Vergleich zu in kalten Werkzeugen umgeformten Proben erzielt werden. Zusätzlich konnte eine Veränderung des Korrosionsverhaltens zwischen den bei unterschiedlichen Werkzeugtemperaturen umgeformten Proben festgestellt werden. Mittels zyklischen potenziodynamischen Polarisationsmessungen in chloridhaltigem Medium wurden unterschiedliche Verläufe der Hystereseschleifen und Verschiebungen des freien Korrosionspotenzials ermittelt. Gestützt durch metallografische Untersuchungen wurden danach unterschiedliche Korrosionsmorphologien bei sonst gleichen mittleren Korngrößen dokumentiert. Diese Beobachtungen sind durch Änderungen im Gefüge auf Subkornebene durch die verzögerte Abkühlung während der Umformung bei 350 °C zu erklären. Der Einfluss verschiedener Abkühlraten auf das Gefüge, die mechanischen Eigenschaften und das Korrosionsverhalten sind Gegenstand weiterer Forschung.